2015
DOI: 10.15850/amj.v2n4.657
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Success Rate of Cardiopulmonary Resuscitation

Abstract: Background: Cardiopulmonary resuscitation (CPR) is a series of actions performed on cardiac arrest patients. Not all patients receiving CPR can survive. The outcome of CPR is influenced by several factors. This study was conducted to determine the success rate of CPR and the factors influencing it in Dr. Hasan Sadikin General Hospital in 2013. Methods: This study was conducted by using 168 patient medical records who underwent CPR and met the inclusion criteria in the Resuscitation Room of Dr. Hasan Sadikin Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Study findings also showed baseline rhythm as a significant predictor of ROSC and CPR–discharge survival so that the highest ROSC and CPR–discharge survival rate was among patients with shockable dysrhythmias (VT). Similarly, previous studies reported shockable dysrhythmias as a significant predictor of ROSC [ 26 , 32 , 33 ]. Strong evidence exists regarding higher CPR success rate among patients with shockable dysrhythmias when defibrillation is used [ 34 ].…”
Section: Discussionsupporting
confidence: 67%
“…Study findings also showed baseline rhythm as a significant predictor of ROSC and CPR–discharge survival so that the highest ROSC and CPR–discharge survival rate was among patients with shockable dysrhythmias (VT). Similarly, previous studies reported shockable dysrhythmias as a significant predictor of ROSC [ 26 , 32 , 33 ]. Strong evidence exists regarding higher CPR success rate among patients with shockable dysrhythmias when defibrillation is used [ 34 ].…”
Section: Discussionsupporting
confidence: 67%
“…1,14 Age, gender, purpose for visit, use of defibrillation, and other characteristics all have an impact. 15,16 Age and gender cannot be changed, but factors such as minimal waste of time at the start of resuscitation operations, timely use of defibrillators, employees' level of knowledge and experience, and pharmaceutical interventions are among the factors that can increase the probability of patient survival with appropriate intervention. 15,17,18 Investigating the factors influencing the success or failure of CPR is medically, economically, and ethically vital to propose adequate and scientific solutions to lessen the obstacles to successful resuscitation.…”
Section: Introductionmentioning
confidence: 99%
“…In some research, the underlying cause is regarded as an important factor 1,14 . Age, gender, purpose for visit, use of defibrillation, and other characteristics all have an impact 15,16 . Age and gender cannot be changed, but factors such as minimal waste of time at the start of resuscitation operations, timely use of defibrillators, employees' level of knowledge and experience, and pharmaceutical interventions are among the factors that can increase the probability of patient survival with appropriate intervention 15,17,18 .…”
Section: Introductionmentioning
confidence: 99%